Plasmodium meets AAV: the (un)likely marriage of parasitology and virology, and how to make the match - Hentzschel, Franziska; Herrmann, Anne-Kathrin; Müller, Ann-Kristin; Grimm, Dirk (FEBS letters, 2016)
The increasing use of screening technologies in malaria research has substantially expanded our knowledge on cellular factors hijacked by the Plasmodium parasite in the infected host, including those that participate in the clinically silent liver stage. This rapid gain in our understanding of the hepatic interaction partners now requires a means to validate and further disentangle parasite-host networks in physiologically relevant liver model systems. Here, we outline seminal work that contributed to our present knowledge on the intrahepatic Plasmodium host factors, followed by a discussion of surrogate models of mammalian livers or hepatocytes. We finally describe how Adeno-associated viruses could be engineered and used as hepatotropic tools to dissect Plasmodium-host interactions, and to deliberately control these networks for antimalaria vaccination or therapy.